Ricardo Guilherme Dicke e o processo de transculturação na l iteratura - Adriana Lins Precioso; louchabel Sarratchara de Fátima Falcão (Estudos de Literatura Brasileira Contemporânea)
The article presents a brief overview of the emergence of the cultural studies in England, the concepts of Stuart Hall and the appropriation of these searches by the literary studies, mainly in Latin America represented through the contributions of Ángel R ama. To exemplify this proposal, we analyze excerpts of the short stories „Toada do Esquecido‟ (2006), „Sinfonia equestre‟ (2006), „A proximidade do mar‟ (2011), „O Velho Moço‟ (2011) and „A perseguição‟ (2011), by Ricardo Guilherme Dicke, writer from the state of Mato Grosso, who promotes the dialogue between regional and global issues by the transculturation bias.